Understanding The Distinctiveness of Pentecostal Spirituality and Its Application to Evangelism In Indonesia - Lumoindong, Gilbert; Lumoindong, Greivance (Eduvest - Journal of Universal Studies, 2025)
Pentecostal spirituality possesses unique characteristics that emphasize direct experiences with the Holy Spirit, including manifestations of spiritual gifts such as speaking in tongues and healing. The Pentecostal Church has rapidly grown in Indonesia, attracting many people with its dynamic spiritual approach that aligns with local cultural values. However, the application of this spirituality in evangelism faces challenges, especially in the context of a multicultural and multi-religious society. Overly expressive approaches may be perceived as foreign by communities with different cultural backgrounds, necessitating adjustments in evangelistic methods to enhance acceptance. This study employs qualitative methods to explore the distinctiveness of Pentecostal spirituality and its implementation within the Indonesian context. The findings indicate that while this spirituality holds significant appeal, the church must maintain a balance between preserving its spiritual identity and adapting to reach a broader audience. By understanding the social and cultural context, the Pentecostal Church is expected to be more effective in its evangelistic mission in Indonesia.